2021
DOI: 10.1097/inf.0000000000003041
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Human Metapneumovirus-associated Lower Respiratory Tract Infections in African Children: Systematic Review and Meta-analysis

Abstract: Background: Human metapneumovirus (hMPV) has been associated with upper and lower respiratory tract infections (LRTI) in children and adults. This systematic review evaluated the epidemiology of hMPV-associated LRTI, including severe acute respiratory infection (SARI) hospitalization or clinically diagnosed severe pneumonia, in African children under 5 years of age. Methods: We searched Science Direct, PubMed, Cochrane Central, Scopus, and WHO regional databases using the terms "("Human metapneumovirus" AND "A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Human metapneumovirus (hMPV) is a viral respiratory pathogen of global importance. 1 , 2 , 3 , 4 First identified in 2001, hMPV is a single‐stranded negative‐sense RNA pneumovirus which, based on serologic studies, has circulated worldwide in human populations for at least seven decades. 5 HMPV is divided into two genetic groups: A and B, which are further differentiated into six known lineages A1, A2a, A2b, A2c, B1, and B2 6 , 7 , 8 and infects all ages, with severe events occurring in children, the elderly, and the immunocompromised.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human metapneumovirus (hMPV) is a viral respiratory pathogen of global importance. 1 , 2 , 3 , 4 First identified in 2001, hMPV is a single‐stranded negative‐sense RNA pneumovirus which, based on serologic studies, has circulated worldwide in human populations for at least seven decades. 5 HMPV is divided into two genetic groups: A and B, which are further differentiated into six known lineages A1, A2a, A2b, A2c, B1, and B2 6 , 7 , 8 and infects all ages, with severe events occurring in children, the elderly, and the immunocompromised.…”
Section: Introductionmentioning
confidence: 99%
“… 9 In children, hMPV is pervasive in early life, causing both upper 10 and severe lower respiratory infections. 1 , 11 Indeed, most children are seropositive for hMPV by age five. 5 , 11 , 12 , 13 Severe hMPV infection is also an important cause in respiratory‐associated childhood hospitalization and has globally been estimated to account for 4–18% of acute lower respiratory infection (ALRI) hospital admissions.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study demonstrated that the detection rate of hMPV in Suzhou was 2.24%. The prevalence rate is 4.7% in Africa ( 11 ) and 3.6% in Bangkok, Thailand ( 12 ). The median age of children infected with hMPV was 16 months, which was significantly lower than that of children infected with HBoV.…”
Section: Discussionmentioning
confidence: 99%
“…Human metapneumovirus (hMPV), is a viral respiratory pathogen of global importance [1][2][3][4] . First identified in 2001, hMPV is a single-stranded negative-sense RNA Pneumovirus which, based on serologic studies, has circulated worldwide in human populations for at least seven decades 5 .…”
Section: Introductionmentioning
confidence: 99%
“…HMPV is divided into two genetic groups: A and B which are further differentiated into 6 known lineages A1, A2a, A2b, A2c, B1, and B2 [6][7][8] and infects all ages, with severe events occurring in children, the elderly, and the immunocompromised 9 . In children, hMPV is pervasive in early-life, causing both upper 10 and severe lower respiratory infections 1,11 . Indeed, most children are seropositive for hMPV by age five 5,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%